Marxist Literary Critique upon Children Literature with Perspective to Movie “The Scrooge: A Christmas Carol” - Ahmad, Imtsal; Murtza, Muniza; Lodhi, Muhammad Arfan (Annals of Human and Social Sciences, 2023)
The purpose of the study is to analyze the Marxist elements such as Class struggle, Class differences, Class division, False consciousness, Bourgeoisie and Proletariat in an animated movie “The Scrooge: A Christmas Carol”. This research applies the theory of Karl Marx on an animated movie “Scrooge: A Christmas Carol”. This movie seems suitable for the application of Marxism as its title has a “word Scrooge”. The current study is exploratory in nature. The data has been collected and analyzed qualitatively. The sample was drawn from the narrative, thematic and visual information present in the movie. The dialogues were transcribed and landscapes were categorized to validate the collection, analysis and interpretation phases of the research. Researchers developed framework of analysis based upon Marxism viewpoint. Analysis and findings presented the Marxism elements. There is a clear division among the society members. There is also a class struggle between upper and lower classes. Bourgeoisie are found in the shape of Scrooge and Jacob. Proletariat is also present in the form of Tom and Bob. The study concludes with substantial recommendation for the future researches to be undertaken in the domain of literary theories and kids’ literature in Pakistan.